Deteksi Plasmodium knowlesi Menggunakan Nested Polymerase Chain Reaction (PCR) di Kecamatan Muara Komam Kalimantan Timur - Zulfa Zahra Salsabila; Rintis Noviyanti; Farah Coutrier; Leily Trianty; Eman Sutrisna; Lantip Rujito (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2022)
Plasmodium knowlesi is a parasite of the genus plasmodium that naturally infects long-tailed macaques (Macaca fascicularis), but currently reported has ability to infect humans. The identification/detection of P. knowlesi can be done using RDT, microscopic, or molecular examinations using nested PCR. Nested PCR is the most sensitive and specific method of examination to date. This study aimed to detect P. knowlesi in humans by RDT, microscopic, and nested PCR examinations. The study was descriptive with a cross-sectional approach, carried out from March to July 2019. The samples in this study were 123 patients who were suspected of being infected with malaria and who underwent laboratory tests at the Muara Komam Health Center. Microscopic examination and RDT examination were carried out at the Muara Komam Health Center, while nested PCR was carried out at the Eijkman Molecular Biology Laboratory Jakarta. The results of RDT and microscopic examinations showed as many as 16 of 123 (13%) malaria-positive samples of P. falciparum and P. vivax, and 10 of 123 (8.1%) malaria-positive samples of P. falciparum and P. vivax. Nested PCR tests targeting the rRNA SSU gene were able to identify P. knowlesi by 6 out of 123 (4.87%). In conclusion, the study showed that Plasmodium knowlesi was detected in humans in Muara Komam, East Kalimantan through nested PCR examination.